2017
DOI: 10.1111/pbi.12790
|View full text |Cite
|
Sign up to set email alerts
|

Functional regulation of Q by microRNA172 and transcriptional co‐repressor TOPLESS in controlling bread wheat spikelet density

Abstract: SummaryBread wheat (Triticum aestivum) spike architecture is an important agronomic trait. The Q gene plays a key role in the domestication of bread wheat spike architecture. However, the regulatory mechanisms of Q expression and transcriptional activity remain largely unknown. In this study, we show that overexpression of bread wheat tae‐miR172 caused a speltoid‐like spike phenotype, reminiscent of that in wheat plants with the q gene. The reduction in Q transcript levels in the tae‐miR172 overexpression tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 47 publications
4
62
0
Order By: Relevance
“…non‐brittle rachises, soft glumes and a free‐threshing characteristic) (Simons et al ., ). By contrast, downregulated expression of Q (Liu et al ., ) or a loss‐of‐function mutation (Fig. a) will recover the q phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…non‐brittle rachises, soft glumes and a free‐threshing characteristic) (Simons et al ., ). By contrast, downregulated expression of Q (Liu et al ., ) or a loss‐of‐function mutation (Fig. a) will recover the q phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…This unusual case likely benefited from the molecular mechanism of Q that negatively regulates wild traits. During wheat domestication, the Q allele originated from a SNP mutation in the miRNA172binding site of the wild-type q allele (Simons et al, 2006), resulting in increased transcription levels via a decrease in miRNA172dependent degradation (Debernardi et al, 2017;Greenwood et al, 2017;Liu et al, 2018;Xu et al, 2018). With dosage effects regulating the phenotype, the upregulated expression of Q improved multiple domestication traits (e.g.…”
Section: Q T Is An Unusual Case For De-domesticationmentioning
confidence: 99%
“…SD is usually controlled by multiple loci. Three well‐known major genes affecting SD, that is Q , C and S1 , were located on chromosomes 5A, 2D and 3D, respectively (Prabhakararao, ; Kato, Sawada, & Miura, ; Liu, Liu, Dong, & Sun, ; Paillard et al, ; Sourdille et al, ; Xu et al, ). It is documented that flowering period (FP), controlled by three main groups of genes: vernalization ( Vrn ), photoperiod ( Ppd ) and earliness per‐se ( Eps ) (Distelfeld, Li, & Dubcovsky, ; Guedira et al, ; Nestor et al, ), is also a key factor for spikelet development in wheat (Guo, Chen, Roeder, Ganal, & Schnurbusch, ; Lewis, Faricelli, Appendino, Valarik, & Dubcovsky, ; Wolde, Trautewig, Mascher, & Schnurbusch, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the miRNA172 binding site in regulating Q expression was supported recently by identification of a novel mutation in the miR172 binding region identified in plants that resembled mutants with an increased copy number and expression of Q , highlighting that mutation of the miRNA binding region alone is sufficient to affect gene function (Greenwood et al ). Similarly, increased expression of the miR172 (tae‐miR172) precursor was shown to correlate with decreased Q gene expression, demonstrating that the Q mutation is not sufficient to completely negate its downregulation by miR172 (Liu et al ). Moreover, a dual‐luciferase sensor system was used to demonstrate that the Q allele has a weaker miR172 target site than q , which reduced the mRNA cleavage efficiency (Debernardi et al ).…”
Section: Investigation Of Domestication Traits To Uncover Genes Contrmentioning
confidence: 99%
“…The function of the Q protein has been investigated, with promising results pointing to a role as a transcriptional repressor that interacts with co‐repression factors (Liu et al ). Analysis of co‐expression profiles of the Q gene and TOPLESS ( TaTPL ), in combination with yeast two hybrid screen and a firefly luciferase complementation imaging assay, showed that Q protein is likely to function as a transcriptional co‐repressor in partnership with Ta TPL (Liu et al ). This finding is supported by the presence of two EAR motifs in Q that are known to interact with TPL/TRP transcriptional co‐repressor (Krogan et al ; Liu et al ).…”
Section: Investigation Of Domestication Traits To Uncover Genes Contrmentioning
confidence: 99%